Crisis as Opportunity? Rethinking Humanitarianism and Refugee Protection in an Age of Retrenchment - Mogstad, Heidi (International migration, 2025)
ABSTRACT The landscape of aid and refugee protection is undergoing profound and unsettling change. Cuts to humanitarian programmes, the rise of privatised and securitised approaches, and the growing reliance on temporary and externalised solutions are reshaping both the lives of displaced people and the institutions meant to protect them. These shifts raise urgent questions not only about the future of asylum and resettlement but also about how we, as researchers or practitioners, should respond. This commentary identifies worrying normative and political developments in Europe and beyond and considers what they mean for us and the people we work with. It also discusses whether the current moment offers an opportunity to radically reimagine and rebuild systems of aid and protection.